The effectiveness of the cardiac resynchronization in a patient with ischemic cardiomyopathy - Diana R. Tudorașcu; Constantin Bătăiosu; Alina Paraschiv; Elena-Anca Târtea; Ionuț Donoiu; Cristina Florescu (Journal of Mind and Medical Sciences)
Cardiac resynchronization therapy (CRT) in multiple and large trials has been demonstrated to improve symptoms and decrease hospitalization and mortality of patients when used in addition to optimal medical therapy. The global mechanical performance of the heart is affected in subjects with heart failure by atrio-ventricular, interventricular, or intraventricular conduction disorders, which lead to the desynchronization of electrical activity. Cardiac resynchronization therapy can effectively improve the clinical and haemodynamic status of these patients. According to literature data, CRT is performed only on well-selected patients (who qualify for CRT based on current indications), and approximately 70% of those patients respond favorably. We present the case of a patient responsive to cardiac resynchronization therapy which led to lowering of his NYHA classification and to improvement of left ventricle hemodynamics. The benefits of cardiac resynchronization therapy were multiple in this case, including improved tolerance to physical exercise and a decreased rate of hospitalization, which overall led to improved quality of life.